PWE-178 Positive Outcomes from a Nutrition Team-Led Radiologically Inserted Gastrostomy (RIG) Service. (4th June 2013) - Ryan-Fisher, C; Burch, N; Trautner, E; Colby, J; Dhillon, M; Harding, J
Abstract : Introduction: Radiologically inserted gastrostomies (RIGs) are an important alternative method of enteral feeding when endoscopic technique is unfeasible. Current published data regarding results post-RIG insertion report varying success, with 30-day mortality ranging from 1–18%. 1, 2 A robust multidisciplinary assessment prior to RIG insertion is vital to ensure clinical suitability. We therefore have examined the case selection and clinical outcomes of our new RIG service. Methods: All patients who underwent RIG placement in our centre between February 2011 and November 2012 were identified. Retrospective analysis of the case notes established the complications post-RIG, the mortality data and which clinicians were involved with the pre-RIG assessment. Two clinicians also independently evaluated the clinical benefit of each RIG using criteria including weight gain, appropriate RIG dwell time and reliance on RIG delivered nutrition to complete proposed treatment (e.g. radiotherapy). Results: 26 patients were identified (mean age 64 years, 54% male). The indications for RIG were head and neck cancers (69%), oesophageal malignancy (15%) and neurological disorders (16%). The Nutrition Team assessed 100% of patients prior to RIG and supported management of all patients post procedure. The mean time between referral and RIG was 6 days (range 2–15 days) and success rate for RIG placement was 96%. The overall 30 day mortality was 4% (1 patient; unrelated to RIG). Early complications (< 24 hours) comprised 1 perforation with pneumoperitoneum. Late complications (2–30 days) included peristomal infection (15%), stomal leakage (12%) and bleeding from RIG site (4%). Complications after 30 days included peristomal infection (8%), inadvertent removal (8%) and RIG tube blockage (8%). Evaluation of clinical benefit concluded that 10% of patients did not benefit from their RIG: one patient with a perforation had a jejunostomy and one patient had leaking from the RIG site that was not utilised. For the remaining 90% of patients the RIG was judged a clinical success. Conclusion: Our data demonstrates an efficient and effective RIG service. Overall complication rates and 30-day mortality are low, reflecting RIG insertion as a safe alternative in those unsuitable for PEG. The assessment of the suitability for RIG by a multi-professional Nutrition Support Team and provision of ongoing support post insertion are key factors associated with a successful RIG service. Prospective data collection with a questionnaire could further evaluate patient experience. Disclosure of Interest: None Declared. References: Lowe AS, Laash HU, Stephenson S, et al. Clin Radiol 2012; 67:843–54. Galaski A, Peng WW, Ellis M, et al. Can J Gastroenterol 2009; 23:109–14.